Political economy in applied linguistics research. (21st December 2016) - Block, David
Abstract : This state-of-the-art review is based on the fundamental idea that political economy should be adopted as a frame for research and discussion in applied linguistics as part of a general social turn which has taken hold in the field over the past three decades. It starts with Susan Gal's (1989) early call for such a move in sociolinguistics and linguistic anthropology, that is, for 'investigations of the links among language structure, language use, and political economy' (Gal1989 : 346), and moves from a consideration of theoretical bases to the discussion and critique of concrete examples of research. Thus, after a fairly detailed discussion of political economy and the key constructs neoliberalism and social class, the paper moves to a review of research in three broad areas. First, it focuses on how issues and constructs from political economy have been incorporated into discussions of education, work and leisure by a growing number of sociolinguists. This is followed by a review of research which has focused specifically on social class as a central organising construct and then a third section on political economy in language teaching and learning research. The review ends with a consideration of the future of political economy in applied linguistics research.